Prestressing Concrete Structures with CFRP Composite Tendons - Katarzyna RYNGIER; Łukasz ZDANOWICZ (Engineering Transactions)
This paper presents a study on prestressing concrete structures with Carbon Fibre Reinforced Polymer (CFRP) tendons. It is an alternative to conventional steel prestressing materials, which distinguishes itself by complete resistance to corrosion, good tensile and fatigue strength and better performance in time under loading. Mechanical properties and examples of prestressing structures with composite tendons are briefly described. The article is focused mainly on describing procedures given by available codes and guidelines. Finally, calculations for an example of a concrete beam prestressed with CFRP tendons are conducted and the results and differences between both codes are presented and summarized.